MCM-41-supported platinum carbonyl cluster-derived asymmetric hydrogenation catalyst - Basu, Susmit; Paul, Himadri; Gopinath, Chinnakonda S.; Bhaduri, Sumit; Lahiri, Goutam Kumar (Journal of Catalysis, 2005)
Anionic platinum carbonyl cluster has been ion paired with cinchonidium groups that are chemically bound to the surface of MCM-41 and fumed silica. In the hydrogenation of methyl pyruvate or acetophenone the fumed silica-based catalyst gives zero enantioselectivity, but under optimum conditions enantiomeric excesses of >90 and similar to40%, respectively, are obtained with the MCM-41-based catalyst. (C) 2004 Elsevier Inc. All rights reserved.
Keywords: asymmetric catalysis; functionalized inorganic oxides; hydrogenation catalysts; platinum carbonyl cluster

Microwave assisted fast and clean conversion of mesylate to azide: synthesis of (1S,2R/1R,2S)-1-azido-2-carbocyclic amines as immediate precursors to versatile 1,2-cis-diamines - Govindaraju, T. (Indian Journal of Chemistry Section B-Organic Chemistry including Medicinal Chemistry, 2006)
An efficient and rapid conversion of mesylate to azide under microwave irradiation has been carried out. It proceeds through inversion of configuration from chiral mesylates to provide optically pure cis-azides, immediate precursors of vicinal-cis-1,2-diamines. These diamines can serve as metal ligands in asymmetric catalysis and their derivatives can be employed as medicinal agents.
Keywords: asymmetric catalysis; Azide; diamines; medicinal agent; mesylate; microwave irradiation

MCM-41-supported ruthenium carbonyl cluster-derived catalysts for asymmetric hydrogenation reactions - Indra, Arindam; Basu, Susmit; Kulkarni, Dhanashree G.; Gopinath, Chinnakonda S.; Bhaduri, Sumit; Lahiri, Goutam Kumar (Applied Catalysis A-General, 2008)
{The anionic ruthenium carbonyl cluster [Ru-4(mu-H)(3)(CO)(12)](-) has been ion-paired with (3-chloropropyl)-trimethoxysilyl-cinchonidium or sparteinium groups chemically bound to the surfaces of MCM-41 [(MCM-41-)(-O)(3)SiCH2CH2CH2NR3+Cl-
Keywords: asymmetric catalysis; functionalized MCM-41; hydrogenation catalysts; nanocatalyst; ruthenium carbonyl cluster

Ultrasound promoted asymmetric transfer hydrogenation of ketones using Ru(II)arene/amino alcohol catalyst system - Shingote, Savita K.; Kelkar, Ashutosh A.; Borole, Yogesh L.; Joshi, Pradip D.; Chaudhari, Raghunath V. (Ultrasonics Sonochemistry, 2008)
Asymmetric transfer hydrogenation of ketones using Ru(II)arene/amino alcohol catalyst system proceeds with significant rate enhancement by ultrasound promotion. Comparison of the silent reactions carried out at 25 degrees C with reactions under sonochemical activation at 25 degrees C clearly showed enhancement in catalytic activity by 5-10 times without significantly affecting the enantioselectivity. (C) 2007 Elsevier B.V. All rights reserved.
Keywords: asymmetric catalysis; transfer hydrogenation; Ultrasound

Synthesis of alpha,beta-unsaturated delta-lactones by vinyl acetate mediated asymmetric cross-aldol reaction of acetaldehyde: mechanistic insights - Kumar, Manjeet; Kumar, Arvind; Rizvi, Masood; Mane, Manoj; Vanka, Kumar; Taneja, Subhash C.; Shah, Bhahwal Ali (European Journal of Organic Chemistry, 2014)
A tandem asymmetric cross-aldol reaction involving the in situ generation of acetaldehyde from vinyl acetate has been developed that may resolve the challenges associated with the handling of acetaldehyde. The simple protocol, mild reaction conditions and unique harmony of an organocatalyst with a biocatalyst make this method a valuable tool for the synthesis of asymmetric beta-hydroxy aldehydes. By using this methodology we have accessed alpha,beta-unstaurated delta-lactones as well as isochromenones with high enantioselectivities from both asymmetric beta-hydroxy aldehydes and ketones. Systemic density functional theory (DFT) studies were also performed to gain mechanistic insights into the role of hydrogen bonding in the asymmetric cross-aldol reaction of acetaldehyde and in the key cis/trans isomerisation step in the synthesis of d-lactones.
Keywords: Aldol reactions; asymmetric catalysis; lactones; reaction mechanisms

Enantioselective synthesis of spirocyclohexadienones by NHC-catalyzed formal [3+3] annulation reaction of enals - Yetra, Santhivardhana Reddy; Mondal, Santigopal; Mukherjee, Subrata; Gonnade, Rajesh G.; Biju, Akkattu T. (Angewandte Chemie-International Edition, 2016)
The enantioselective synthesis of pyrazolone-fused spirocyclohexadienones was demonstrated by the reaction of alpha,beta-unsaturated aldehydes with alpha-arylidene pyrazolinones under oxidative N-heterocyclic carbene (NHC) catalysis. This atom-economic and formal [3+3] annulation reaction proceeds through a vinylogous Michael addition/spiroannulation/dehydrogenation cascade to afford spirocyclic compounds with an all-carbon quaternary stereocenter in moderate to good yields and excellent ee values. Key to the success of the reaction is the cooperative NHC-catalyzed generation of chiral alpha,beta-unsaturated acyl azoliums from enals, and base-mediated tandem generation of dienolate/enolate intermediates from pyrazolinones.
Keywords: annulation reactions; asymmetric catalysis; N-heterocyclic carbenes; organocatalysis; spiro compounds

NHC-catalyzed desymmetrization of N-aryl maleimides leading to the atroposelective synthesis of N-Aryl succinimides - Barik, Soumen; Shee, Sayan; Das, Soumik; Gonnade, Rajesh G.; Jindal, Garima; Mukherjee, Subrata; Biju, Akkattu T. (Angewandte Chemie-International Edition, 2021)
Although the construction of axially chiral C-C bonds leading to the atroposelective synthesis of biaryls and allied compounds are well-known, the related synthesis of compounds bearing axially chiral C-N bonds are relatively rare. Described herein is the N-heterocyclic carbene-catalyzed atroposelective synthesis of N-aryl succinimides having an axially chiral C-N bond via the desymmetrization of N-aryl maleimides. The NHC involved intermolecular Stetter-aldol cascade of dialdehydes with prochiral N-aryl maleimides followed by oxidation afforded N-aryl succinimides in good yields and ee values. Preliminary studies on rotation barrier for the C-N bond, the temperature dependence, and detailed DFT studies on mechanism are also provided.
Keywords: asymmetric catalysis; axial chirality; desymmetrization; N-heterocyclic carbenes; organocatalysis